2011
DOI: 10.1002/aic.12558
|View full text |Cite
|
Sign up to set email alerts
|

Parametric analysis of Fischer‐tropsch synthesis in a catalytic microchannel reactor

Abstract: in Wiley Online Library (wileyonlinelibrary.com).Fischer-Tropsch synthesis (FTS) involves highly exothermic conversion of syngas to a wide range of hydrocarbons, but demands isothermal conditions due to the strong dependence of product distribution on temperature. Running FTS in microchannel reactors is promising, as the sub-millimeter dimensions can lead to significant intensification that inherently favors robust temperature control. This study involves computerbased FTS simulations in a heat-exchange integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 27 publications
2
12
0
1
Order By: Relevance
“…17 -21 Recently, strongly exothermic processes such as Fischer-Tropsch (FT) synthesis and FT wax hydrocracking, both of which demand strict temperature control, have been simulated in heat-exchange integrated microchannel reactors involving coupling of catalytic reaction and cooling channels. 22,23 These studies clearly showed that effective temperature control in the reaction channels can be obtained by fast heat exchange between the adjacent channels.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…17 -21 Recently, strongly exothermic processes such as Fischer-Tropsch (FT) synthesis and FT wax hydrocracking, both of which demand strict temperature control, have been simulated in heat-exchange integrated microchannel reactors involving coupling of catalytic reaction and cooling channels. 22,23 These studies clearly showed that effective temperature control in the reaction channels can be obtained by fast heat exchange between the adjacent channels.…”
Section: Introductionmentioning
confidence: 93%
“…The coupling of an exothermic and an endothermic reaction, both running in adjacent channels of the same reactor has been studied for several systems such as oxidation assisted steam reforming of hydrocarbons to achieve efficient hydrogen and synthesis gas production in compact units . Recently, strongly exothermic processes such as Fischer‐Tropsch (FT) synthesis and FT wax hydrocracking, both of which demand strict temperature control, have been simulated in heat‐exchange integrated microchannel reactors involving coupling of catalytic reaction and cooling channels . These studies clearly showed that effective temperature control in the reaction channels can be obtained by fast heat exchange between the adjacent channels.…”
Section: Introductionmentioning
confidence: 99%
“…FTS catalysts have been applied to conventional reactors such as the multi-tubular fixed bed reactor (TFBR), slurry bubble column reactor (SBCR), and fluidized bed reactor (FBR) [9][10][11]. Furthermore, micro-channel technology has been recently used to minimize heat transfer resistance [1,[12][13][14][15] high productivity, and thermally stable operation of the synthesis reactor.…”
Section: Introductionmentioning
confidence: 99%
“…With the increasing instability in the price of crude oil and the depletion of natural crude oil resources, the production of synthetic fuels by the gas-to-liquid (GTL) process has continued to receive more attention [1]. The key concept of the GTL process is chemical conversion of natural gas to synthesis gas (syngas; mixture of CO and H 2 ), followed by conversion of syngas to longer chain hydrocarbons, which are typically in the range of hydrocarbons used in liquid transportation fuels, via Fischer-Tropsch synthesis (FTS) [2].…”
Section: Introductionmentioning
confidence: 99%
“…두 번째, 몇 가지의 대 표적인 화학종의 개별적인 반응속도식과 그 외에 양 이 적은 고분자 부분을 하나의 반응속도식으로 묶어 서 적용하는 경우 [9][10][11]. 세 번째, ASF 이론을 사용하여 식 (5)과 같이 chain growth factor 를 이용해 화학종 별 반응속도식을 추정하는 경우다 [1,[12][13]. …”
unclassified